2018
DOI: 10.4236/fns.2018.92011
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Bone Mineral Density and Obesity in Women

Abstract: The aim of this study was to determine the relationship between obesity and osteoporosis. A total of 30 Saudi women, 20 -50 years of age, were randomly selected. We calculated the body mass index (BMI) and determined the lumbar and femur bone mineral density using dual-energy X-ray absorptiometry (DXA). We examined the interaction between obesity and bone mineral density (BMD) using logistic regression after adjusting for age, a family history of osteoporosis, maternal fractures, smoking, and sedentary lifesty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several studies demonstrated high danger of break and osteoporosis in individuals with high BMI [48,49]. It turns out also, that obesity may not confer greater protection against fracture in those people [50].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies demonstrated high danger of break and osteoporosis in individuals with high BMI [48,49]. It turns out also, that obesity may not confer greater protection against fracture in those people [50].…”
Section: Resultsmentioning
confidence: 99%